Automatic egg boiler / Abdul Hafiz Abdul Rahman, Tasneem Ghaffa and Nurul Atikah Mohmad Amin - Abdul Rahman, Abdul Hafiz; Ghaffa, Tasneem; Mohmad Amin, Nurul Atikah (2013)
Facing with the growth of the technology has made us aware of the mankind’s problem. People nowadays tend to looking for something that do not burden their busy life and also will make their life easier than before. So, we come out with the project of automatic egg boiler to ease all of the people in this modem world on boiling the egg without any mistakes and of course, save their time and energy. An automatic egg boiler that we are going to produce is an appliance that will make the eggs boiled in two different ways, which are half boiled eggs and hard boiled eggs. In making this automatic egg boiler, we are using PIC to set the time for the water to be pumped out from the beaker outside the main container before it is enter the secondary container where the eggs will be boiled. After a while, the heater will be heated and the water will start to boil the eggs. By using the button provided, we can choose whether we want the eggs to be half boiled of hard boiled. The time needed for the two different kind of boiling is not the same. After the eggs have been boiled as needed, the hot water from the secondary container will be thrown up to the bottom of the main container. We are using the stepper motor to rotate the secondary container at 360 until the hot water safely removed from the secondary container.